Optimalisasi Pembelajaran Akidah Akhlak melalui Media Quizizz untuk Meningkatkan Prestasi Belajar Siswa - Muhammad Anas Maarif; Susi Susanti Lenda; Muhammad Husnur Rofiq; Ismawati Ismawati; Ardianto Ardianto (Institut Agama Islam Daruttaqwa Gresik, 2025)
This research aims to find out how to implement learning using Quiziz media to improve the learning achievement of students in moral beliefs in class VII A at MTsN 1 Mojokerto. This Research uses qualitative Research. This Research approach uses a case study approach. The results of this study show that 1. Learning planning with quizizz media on the subjects of moral creed, namely by adjusting the curriculum used in considering the characteristics of grade 7A students. In learning activities, teachers are expected to use lesson plans or teaching modules that are in accordance with the curriculum used. 2. Implementation of learning with quizizz media on moral creed subjects. That is, the teacher provides understanding to students through practice questions given by the teacher. 3. Evaluate learning with quizizz media on moral creed subjects. Teachers measure students' abilities using various methods, such as media or direct observation. The purpose of this measurement is to gather relevant and measurable information regarding students' understanding, knowledge, skills and attitudes.